The study of EDLC device with high electrochemical performance fabricated from proton ion conducting PVA-based polymer composite electrolytes plasticized with glycerol - Brza, Mohamad A.; Aziz, Shujahadeen; Anuar, Hazleen; Dannoun, Elham M.A; Ali, Fathilah; Abdulwahid, Rebar T.; Al-Zangana, Shakhawan; Kadir, Mohd F. Z. (MDPI, 2020)
In the present work, a novel polymer composite electrolytes (PCEs) based on poly(vinyl alcohol) (PVA): ammonium thiocyanate (NH4SCN): Cd(II)-complex plasticized with glycerol (Gly) are prepared by solution cast technique. The film structure was examined by XRD and FTIR routes. The utmost ambient temperature DC ionic conductivity (σDC) of 2.01 × 10−3 S cm−1 is achieved. The film morphology was studied by field emission scanning electron microscopy (FESEM). The trend of σDC is further confirmed with investigation of dielectric properties. Transference numbers of ions (tion) and electrons (tel) are specified to be 0.96 and 0.04, respectively. Linear sweep voltammetry (LSV) displayed that the PCE potential window is 2.1 V. The desired mixture of activated carbon (AC) and carbon black was used to fabricate the electrodes of the EDLC. Cyclic voltammetry (CV) was carried out by sandwiching the PCEs between two carbon-based electrodes, and it revealed an almost rectangular shape. The EDLC exhibited specific capacitance, energy density, and equivalent series resistance with average of 160.07F/g, 18.01Wh/kg, and 51.05Ω, respectively, within 450 cycles. The EDLC demonstrated the initial power density as 4.065 × 103 W/Kg.